2011
DOI: 10.1161/circresaha.111.250282
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Exerts an Antiproliferative Effect on Adult Cardiac Progenitor Cells Through IGFBP3

Abstract: Rationale Recent work in animal models and humans has demonstrated the presence of organ-specific progenitor cells required for the regenerative capacity of the adult heart. In response to tissue injury, progenitor cells differentiate into specialized cells, while their numbers are maintained through mechanisms of self-renewal. The molecular cues that dictate the self-renewal of adult progenitor cells in the heart, however, remain unclear. Objective Herein, we investigate the role of canonical Wnt signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 55 publications
5
73
0
Order By: Relevance
“…The recognition that the adult heart harbors a compartment of multipotent c-kit-positive cardiac stem cells (CSCs) (15)(16)(17)(18)(19)(20)(21)(22)(23) and other progenitor cell classes (24)(25)(26)(27)(28)(29) capable of differentiating into cardiomyocytes and coronary vessels has raised the challenging question concerning their embryologic origin and role in cardiac cell turnover and regeneration. CSCs are stored in interstitial structures with the characteristics of stem cell niches and can divide symmetrically and asymmetrically, with the ability to self-renew and form a committed progeny (17,21,30).…”
Section: Introductionmentioning
confidence: 99%
“…The recognition that the adult heart harbors a compartment of multipotent c-kit-positive cardiac stem cells (CSCs) (15)(16)(17)(18)(19)(20)(21)(22)(23) and other progenitor cell classes (24)(25)(26)(27)(28)(29) capable of differentiating into cardiomyocytes and coronary vessels has raised the challenging question concerning their embryologic origin and role in cardiac cell turnover and regeneration. CSCs are stored in interstitial structures with the characteristics of stem cell niches and can divide symmetrically and asymmetrically, with the ability to self-renew and form a committed progeny (17,21,30).…”
Section: Introductionmentioning
confidence: 99%
“…Wnt signal strength has been shown to control the balance between self renewal and differentiation (46). We found that EC-educated MniPSC-MPP downregulated targets of the Wnt/β-catenin pathway relative to EC-naive MniPSC-MPP, which is not surprising given that ECs express Wnt pathway inhibitors DKK1 (47), DKK3 (15), IGFPB2 (48), and IGFBP3 (49). Wnt signaling has been shown to regulate the Notch pathway in normal (50)(51)(52) and malignant hematopoiesis (53,54).…”
Section: Discussionmentioning
confidence: 66%
“…The upregulation of MYH11 might suggest spontaneous differentiation of cells into smooth muscle cells (one of the cell lines that CSCs are committed to) through passages. It was shown that members of IGFBP family such as IGFBP4 and IGFBP3, which are independent of binding to insulin growth factor, are involved in the processes of cardiogenesis [48][49][50]. A new subset of cardiac precursor cells that expressed insulin-like growth factor 1 receptor (IGF-1R) was found to have higher proliferation and myogenic differentiation potential compared with other CSCs subgroups [51].…”
Section: Discussionmentioning
confidence: 99%